IMPLEMENTASI KEBIJAKAN PENGEMBANGAN OBYEK WISATA PANTAI PADA DINAS KEBUDAYAAN DAN PARIWISATA DI KOTA MAKASSAR - Dianindarwati, A; Setiawati, Budi; Usman, Jaelan (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThe purpose of the study was to find out the implementation of the policy for developing coastal tourism objects at the cultural and tourism service in Makassar City. This study used qualitative research. The results showed that the implementation of the policy for the development of coastal tourism objects at the Department of Culture and Tourism in Makassar City, viewed from the aspects: 1. Communication, the Makassar City Culture and Tourism Office was very good because the service office always prioritized communication in every divisions. in each office to run according to the SOP in each office in realizing good service. 2. Resources, the Culture and Tourism Office were good at providing natural resources in each tourist attraction so that each tourist attraction had good natural resources in attracting people who came to take a vacation, 3. Disposition of the Office of Culture and the Makassar City Tourism Office had been said to be good because each employee's office had been given training on tourism development policies in the city of Makassar, 4. The bureaucratic structure of the official was good because the bureaucratic structure in each office had implemented a bureaucratic structure that had been determined directly from the head office.Keywords: Policy implementation, tourism object